Relationship between efficiency and profitability: The case of Czech swine sector - Hedija, Veronika; Kuncová, Martina (Spanish Journal of Agricultural Research, 2021)
Aim of study: To examine the link between economic efficiency and profitability of firms belonging to the swine sector.Area of study: This study is devoted to the Czech swine sector that forms the traditional and essential part of agriculture in the Czech Republic.Material and methods: Data from the Albertina CZ Gold Edition database for the period 2008-2017 were used. To evaluate the economic efficiency, the data envelopment analysis models are applied. Return on equity, return on assets and return on sales are used to measure profitability. To assess the relationship between economic efficiency and profitability, the Pearson correlation coefficient is used.Main results: The results demonstrate that there is no clear link between the economic efficiency of firms and their profitability in this industry. The correlation between all three profitability ratios and efficiency score were predominantly positive but not statistically significant in many cases. The economies of scale and scope and the construction of profitability indicators could be the main factors explaining the fact that companies achieving higher efficiency are not also more profitable.Research highlights: The study provides material useful to owners, managers, and customers of Czech agriculture firms. It identifies the relatively high efficiency of firms measured relatively to the best Czech company. In the European context, however, the efficiency of Czech firms belonging to the swine sector is low. It also reveals that the profitability of the firms is not a representative proxy for economic efficiency.